STUDY ON OCHRATOXIN A AND ZEARALENONE CONTENT IN CORN GRAINS FROM DIFFERENT AREAS OF BACAU COUNTY - Sonia AMARIEI (Stefan cel Mare University of Suceava, 2020)
The purpose of the study is to evaluate the contamination with mycotoxins of the corn cultures in the county of Bacau, in correlation with the geographical and agro-climatic conditions of this area. Romania is one of the largest corn producers from the European Union and harvested almost 10746.4 thousand of tons in 2016, 14326.1 thousand of tons in 2017, 18353 thousand of tons in 2018, 16990 thousand of tons in 2019, over 1.5 million tons going into exports in countries both from the EU and outside. The main mycotoxins identified in the corn cultures in the county of Bacau are: Aflatoxins, Deoxynivalenol, Zearalenone, Toxin T2 and HT2, Fumonisins. The study aimed to determine the quantity of ochratoxin and zearalenone from corn kernels harvested in the county of Bacau. The identified mycotoxins do not exceed the maximum limits according to Reg. (CE) 1881/2006, which regulates the maximum limits for certain contaminants in food products.